Digitalisasi Identitas Lokal: Optimalisasi Website untuk Memperkuat Daya Tarik Desa Pait, Kasembon, Malang - Moh. Pebrianto; Nanda Harda Pratama Meiji; Ahmad Arif Widianto; Luly Triningsih (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The optimization of village websites is a strategic step in leveraging information technology to enhance the potential of Pait Village, Kasembon District, Malang Regency, as a tourist destination. Using a community development approach, this initiative actively involves local community participation in creating and managing website content that reflects local wisdom. Training and technical assistance were provided to village officials and residents to improve human resource capacity for sustainable website management. The results indicate significant improvements in the website’s design and content, along with increased community engagement in the development process. With this optimization, the village website functions not only as a medium for documenting village activities and promoting tourism but also as a branding tool that strengthens the local identity of Pait Village. Moving forward, sustained website management is expected to boost tourist visits and support the welfare of the village community through local economic growth. Keywords: Village website optimization, Pait Village, community-based tourism, community empowerment, information technolog